Academic Publishing in Nepal - Ravi Shankar, Pathiyil; KC, Bhuvan; Amgain, Kapil (Journal of Karnali Academy of Health Sciences, 2022)
Globally academic publishing is a high-profit industry. Most of the work associated with manuscripts is carried out by academics for free. The article examines the academic publishing industry in Nepal. Most journals in Nepal are published by institutions or societies. Most do not have article processing charges. The issue of Nepalese authors having to pay for publishing in international journals as Nepal is upgraded to a lower-middle-income country is also mentioned.